SIJARWA: Android-Based Javanese Script Sandhangan Learning Media Development Innovation - Jaenal Rojikin; Rahutami; Suryantoro (International Journal of Integrative Sciences, 2023)
This study aims to develop an android-based learning media for introducing Javanese script to fourth graders of an elementary school named SIJARWA. The type of research conducted is research and development using the R&D method with the ADDIE model which includes analysis, design, development, implementation, and evaluation. The validation carried out by the researchers included the validation of material experts, linguists, and props experts. The data analysis technique used is the feasibility of media quality using a questionnaire instrument. The results showed that the SIJARWA learning media is suitable for use as a learning resource for fourth- grade elementary school students